PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT ESHAN GEMILANG PRATAMA KOTA TANGERANG - Nova Kurnia Dewi; Sutrisno (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of motivation and work discipline on employee performance at PT Eshan Gemilang Pratama Kota Tangerang. The research method used in the study is the Quantitative Method. The sampling technique used is saturated sampling with 57 respondents. Data collection using questionnaires while data analysis is carried out using the Validity Test analysis, Reliability Test, Classical Assumption Test (Normality Test, Kolmogorov Smirnov Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Glejser Test Model) Simple Linear Regression Test, Multiple Linear Regression Test, Correlation Coefficient Test, Determination Test, Partial Test (t Test) Simultaneous Test (f Test). At a significance rate of 5%, the results of the study found that: The results of the study showed that motivation has a significant effect on employee performance partially, indicated by the simple linear regression equation Y = 0.403 + 0.954 X1 showing a positive value which means there is a change in the same direction, where if work motivation (X1) increases by one unit, employee performance (Y) will also increase. This is evidenced by the hypothesis test obtained a calculated t value> t table (25.290> 2.004) and reinforced by a significance value of <0.05 (0.000<0.05). Work Discipline has a significant effect on employee performance partially indicated by the simple linear regression equation Y = 3.134 + 0.917 X2, where the coefficient value is positive, meaning that if work discipline increases, employee performance will also increase. This is evidenced by the hypothesis test obtained a calculated t value> t table (24.455> 2.004) and reinforced by a significance value of <0.05 (0.000<0.05). The results of the study on employee performance are shown by the multiple linear regression equation Y = 0.805 + 0.513 X1 + 0.451 X2, where the coefficient value is positive, which means that there is a change in the same direction, where work motivation and work discipline do not change or are fixed, then employee performance will remain positive. This is evidenced by the results of the simultaneous hypothesis test obtained the value of Fcount> Ftable (469.202> 3.16) and strengthened by a significance value of <0.05 (0.000 <0.05). The results of the determination coefficient test of the work motivation variable (X1) and work discipline (X2) have an influence of 97.2% on employee performance at PT Eshan Gemilang Pratama. Thus Ho is rejected and H3 is accepted. This means that there is a significant simultaneous influence between work motivation (X1) and work discipline (X2) on employee performance (Y).